Effects of yeast immobilization on bioethanol production. (2nd January 2014) - Borovikova, Diana; Scherbaka, Rita; Patmalnieks, Aloizijs; Rapoport, Alexander; Rapoport, Alexander; Heipieper, Hermann J.
Abstract The current study evaluated a newer method, which includes a dehydration step, of immobilizing Saccharomyces cerevisiae L‐77 and S. cerevisiae L‐73 onto hydroxylapatite and chamotte ceramic supports. The efficiency of cell immobilization on chamotte was significantly higher than hydroxylapatite. Immobilized yeast preparations were investigated for their ethanol‐producing capabilities. The glucose concentration in a fermentation medium was 100 mg/mL. Immobilized preparations produced the same amount of ethanol (48 ± 0.5 mg/mL) as free cells after 36 H of fermentation. During the early stages of fermentation, immobilized yeast cells produced ethanol at a higher rate than free cells. Yeast preparations immobilized on both supports (hydroxylapatite and chamotte) were successfully used in six sequential batch fermentations without any loss of activity. The chamotte support was more stable in the fermentation medium during these six cycles of ethanol production. In addition to the high level of ethanol produced by cells immobilized on chamotte, the stability of this support and its low cost make it a promising material for biotechnologies associated with ethanol production.